The systemic inflammatory response index is associated with chronic kidney disease in patients with hypertension: data from the national health and nutrition examination study 1999–2018 - Yani Wang; Lihua Liao; Qian Guo; Ying Liao; Xueqin Lin; Huilan Li; Lin Deng; Yufei Deng; Danni Guo; Kaihong Chen; Yong Fang (Renal Failure)
Background Studies have shown that in hypertensive patients, chronic kidney disease (CKD) is associated with a poor prognosis. Inflammation is a highly important factor in the progression of CKD. Detecting systemic inflammation and intervening promptly in patients with hypertension may help reduce the risk of CKD. The systemic inflammatory response index (SIRI) is a tool used to measure the systemic inflammatory response, but its relationship with CKD in patients with hypertension remains uncertain.Methods We utilized data from the National Health and Nutrition Examination Survey (NHANES), which was conducted between 1999 and 2018. The analysis included a total of 20,243 participants, categorized into three groups based on SIRI tertiles. Logistic regression analysis and restricted cubic spline analysis were used to examine the relationship between the SIRI and CKD.Results In patients with hypertension, there was a notable relationship between the SIRI and the odds of developing CKD. After full adjustment, there was a 31% greater likelihood of developing CKD associated with each incremental increase of 1 unit in the SIRI (OR: 1.31, 95% CI: 1.24–1.39, p < 0.001). The groups with greater SIRI values exhibited greater odds of developing CKD than did the T1 group (T2: OR: 1.20, 95% CI: 1.04–1.38, p = 0.015; T3: OR: 1.69, 95% CI: 1.47–1.94, p < 0.001).Conclusion A high SIRI is associated with an increased risk of CKD in hypertensive patients. The greater the SIRI is, the greater the risk of CKD in hypertensive patients.